Heath care performance in the training of the gastroenterology resident - Jesús Fernández Duharte; Yaritza Tardo Fernández (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The heath care performance of the gastroenterology resident conditions his professional pertinence in the public health as for the diagnosis and treatment of patients with digestive diseases. Objective: To deepen in the training process of the gastroenterology resident. Method: An epistemologic analysis and factic diagnosis of the training process of the gastroenterology resident regarding the care to patients with digestive neoplasm in Juan Bruno Zayas Teaching General Hospital from Santiago de Cuba during the biennium from the observation of the health care performance, the survey to residents and interviews to specialists of this branch in the province. Results: There were inconsistencies in this training as a result of a visible polarization doctor-tools of practice in the care, orientated to the endoscopic and therapeutic digestive endoscopy, contrary to the preventive procedure. Conclusion: It could be confirmed that the care dimension had not been sufficiently systematized while giving care to patients with digestive neoplasm taking into account the training integration of prevention, diagnosis and therapeutics in the endoscopic praxis of this professional.